COPB1-knockdown induced type I interferon signaling activation inhibits Chlamydia psittaci intracellular proliferation - Li, Nana; Yang, Huiying; Zhang, Shan; Jiang, Yufei; Lin, Yinhui; Chen, Xiaoxiao; Zhang, Yuchen; Yu, Yonghui; Ouyang, Xuan; Cui, Yujun; Song, Yajun; Jiao, Jun (Frontiers in Microbiology, 2025)
ObjectiveChlamydia psittaci is a zoonotic pathogen that causes an acute disease known as psittacosis. To establish infection in host cells, Chlamydia manipulates the host cell’s membrane trafficking pathways.MethodsIn this study, using fluorescently labeled C. psittaci and screening a human membrane trafficking small interfering RNA (siRNA) library, we identified 34 host proteins that influenced C. psittaci infection in HeLa cells.ResultsAmong these, knockdown (KD) of two genes encoding subunits of the coatomer complex I (COPI) inhibited the pathogen’s intracellular survival. Specifically, the knockdown of COPB1, a COPI subunit, significantly reduced the intracellular proliferation of C. psittaci. Mechanistically, we found that type I interferon negatively affected C. psittaci infection. Moreover, COPB1 KD disrupted the homeostasis of STING, preventing its retrieval from the Golgi back to the endoplasmic reticulum (ER), which in turn activated type I interferon signaling.ConclusionTogether, our findings advance the understanding of the mechanisms underlying Chlamydia infection and offer potential avenues for the development of new anti-C. psittaci strategies.